The Effectiveness of the Educational Field to Developing the Skills of Dribbling and Shooting of Football For Youth - Husam Kadhim Jawad; Mazin Abdul Hedi Ahmed; Asaad Hussein Abd Alrazaq (Indian Journal of Forensic Medicine & Toxicology, 2021)
The importance of the research lies in preparing an educational field in developing the skills of dribblingand shooting football for cubs, depending on the stock of motor skills that were learned in a previous period,which are prerequisites for motor learning and achieving good technical performance that secures a levelof performance. As for the research problem: through the experience of field researchers, they noticed thatthere is a weakness in the performance of the dribbling and scoring skills of the young players, and that thelevel of dribbling and scoring performance is not commensurate with the level required for this stage, a thedirect interest in dribbling and scoring through skill exercises is not sufficient to reach high performancewithout concern for the effectiveness of the educational field, and this is what the cubs’ teams suffer at leastin our country, and if there is interest in these variables, then it is random and includes training that doesnot distinguish between the important and most important dimensions and components of these variables.Therefore, the researchers decided to prepare an educational field in developing the skills of dribbling andscoring football for cubs in order to reach the desired and intended achievement.